Chappie: the art of the movie - Aperlo, Peter E.; Blomkamp,Neill
Chappie is an upcoming film directed by Neill Blomkamp District 9 and Elysium, written by Neill Blomkamp y Terri Tatchell. The film stars Sharlto Copley Elysium, The A-Team, Dev Patel Slumdog Millionaire, Ninja and Yo-Landi Vi$er, Jose Pablo Cantillo The Walking Dead, with Sigourney Weaver Aliens, Avatar, and Hugh Jackman Wolverine, X-Men